Cultivating Green Human Resource Management (GHRM) to Small and Medium-Sized Enterprises (SMEs) for Green Performance - Theresia Marditama; Mohd Yusoff Yusliza (Greenation Research & Yayasan Global Resarch National, 2023)
At the present time in Indonesia, businesses that fall into the category of